Nano Uncaria gambir as Chemopreventive Agent Against Breast Cancer - Wardana AP; Aminah NS; Kristanti AN; Fahmi MZ; Zahrah HI; Widiyastuti W; Ajiz HA; Zubaidah U; Wiratama PA; Takaya Y (International Journal of Nanomedicine, 2023)
Andika Pramudya Wardana,1 Nanik Siti Aminah,1,2 Alfinda Novi Kristanti,1,2 Mochamad Zakki Fahmi,1 Haninda Iffatuz Zahrah,3 W Widiyastuti,4 Hendrix Abdul Ajiz,4 Ummi Zubaidah,5 Priangga Adi Wiratama,6 Yoshiaki Takaya7 1Department of Chemistry, Faculty of Science and Technology, Universitas Airlangga, Surabaya, East Java, Indonesia; 2Biotechnology of Tropical Medicinal Plants Research Group, Universitas Airlangga, Surabaya, East Java, Indonesia; 3Faculty of Dental Medicine, Universitas Airlangga, Surabaya, East Java, Indonesia; 4Department of Chemical Engineering, Faculty of Industrial Technology and Systems Engineering, Institut Teknologi Sepuluh Nopember, Surabaya, East Java, Indonesia; 5Department of Biology, Faculty of Science and Technology, Universitas Airlangga, Surabaya, East Java, Indonesia; 6Department of Anatomic Pathology, Faculty of Medicine, Universitas Airlangga – RSUD Dr. Soetomo Academic General Hospital, Surabaya, East Java, Indonesia; 7Faculty of Pharmacy, Meijo University, Nagoya, JapanCorrespondence: Nanik Siti Aminah, Department of Chemistry, Faculty of Science and Technology, Universitas Airlangga, Kampus C-UNAIR, Jl. Mulyorejo, Surabaya, 60115, Indonesia, Tel +62-31-5936501, Fax +62-31-5936502, Email nanik-s-a@fst.unair.ac.idBackground: Breast cancer is one of the main causes of death in women. Uncaria gambir is an Indonesian herbal plant that can be used as an anti-cancer. However, herbal medicines have low bioavailability, which affects their bioactivity. Nanoencapsulation can increase bioavailability and stability of bioactive compounds in herbal medicines.Purpose: This recent finding tried to unravel anti-cancer and chemopreventive of U. gambir nano-encapsulated by Na-alginate.Study Design: U. gambir bioactive compounds were isolated and characterized using UV–Vis spectrometer, FTIR, NMR and HR-MS. U. gambir extract was nanoencapsulated using Na-alginate. Anti-cancer effect was assessed by MTT assay towards T47D cell. Meanwhile, a chemopreventive analysis was carried out in breast cancer mice-induced benzo[α]pyrene. The healthy mice were divided into 8 groups comprising control and treatment.Results: Elucidation of U. gambir ethyl acetate extract confirmed high catechin content, 89.34% (w/w). Successful nanoencapsulation of U. gambir (G-NPs) was indicated. The particle size of G-NPs was 78.40 ± 12.25 nm. Loading efficiency (LE) and loading amount (LA) of G-NPs were 97.56 ± 0.04% and 32.52 ± 0.01%, respectively. G-NPs had an EC50 value of 10.39 ± 3.50 μg/mL, which was more toxic than the EC50 value of extract towards the T47D cell line. Administration of 200 mg/kg BW G-NPs to mice induced by benzo[α]pyrene exhibited SOD and GSH levels of 13.69 ng/mL and 455.6 ng/mL. In addition, the lowest TNF-α level was 27.96 ng/mL. A dose of 100 mg/kg BW G-NPs could best increase CAT levels by 7.18 ng/mL. There was no damage or histological abnormalities found in histological analysis of the breast tissue in the group given 200 mg/kg BW G-NPs.Keywords: breast cancer, chemopreventive, cytotoxicity, nanoencapsulation, U. gambir